Man and Environment in Contemporary Fiction - Nosek, Jan (Univerzita Pardubice, 2023)
This bachelor thesis deals with the depiction of the relation between man and environment in three novels by authors Powers, Proulx, and Pancake. It uses theoretical concepts such as ecocriticism, environmental ethics, and the sociology of generations. These concepts are introduced in the first chapter. All remaining chapters focus on the analysis of the aforementioned novels. The aim of this work is to determine how the characters perceive nature and why they perceive it in a particular way.
Člověk a životní prostředí v současné próze
Keywords: ekokriticismus; antropocentrismus; biocentrismus; environmentální etika; generační sociologie; ecocriticism; anthropocentrism; biocentrism; environmental ethics; sociology of generations